CD8+ T cells of Listeria monocytogenes‐infected mice recognize both linear and spliced proteasome products. Issue 5 (16th March 2016) - Platteel, Anouk C. M.; Mishto, Michele; Textoris‐Taube, Kathrin; Keller, Christin; Liepe, Juliane; Busch, Dirk H.; Kloetzel, Peter M.; Sijts, Alice J. A. M.
Abstract : Here we show that proteasome‐catalyzed peptide splicing, producing spliced peptides, expands the number of Listeria monocytogenes ‐derived epitope candidates substantially and that different linear and spliced epitopes, sharing sequence similarity, can be recognized by cross‐reactive CD8 + T cells in L. monocytogenes ‐infected mice. Abstract : CD8 + T cells responding to infection recognize pathogen‐derived epitopes presented by MHC class‐I molecules. While most of such epitopes are generated by proteasome‐mediated antigen cleavage, analysis of tumor antigen processing has revealed that epitopes may also derive from proteasome‐catalyzed peptide splicing (PCPS). To determine whether PCPS contributes to epitope processing during infection, we analyzed the fragments produced by purified proteasomes from a Listeria monocytogenes polypeptide. Mass spectrometry identified a known H‐2K b ‐presented linear epitope (LLO296‐304 ) in the digests, as well as four spliced peptides that were trimmed by ERAP into peptides with in silico predicted H‐2K b binding affinity. These spliced peptides, which displayed sequence similarity with LLO296‐304, bound to H‐2K b molecules in cellular assays and one of the peptides was recognized by CD8 + T cells of infected mice. This spliced epitope differed by one amino acid from LLO296‐304 and double staining with LLO296‐304 ‐ and spliced peptide‐folded MHC multimers showed that LLO296‐304 and its spliced variant were recognized by the same CD8 + T cells. Thus, PCPS multiplies the variety of peptides that is processed from an antigen and leads to the production of epitope variants that can be recognized by cross‐reacting pathogen‐specific CD8 + T cells. Such mechanism may reduce the chances for pathogen immune evasion.